Visual Identity of Contemporary Art Museums on Facebook, Instagram and Web: A Comparative Analysis - López-Iglesias, Matías; Tapia-Frade, Alejandro; Carreño Villada, Jose Luis (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Analysis of the visual identity of 40 contemporary art museums, observing their digital presence. 27 characteristic variables of the Se icon were identified, contrasting its visual presence on social networks and the web. The main results indicate the majority use of logos and imagotypes, with a rectangular archetype and non-figurative iconicity. Black monochrome predominates. The typography being composed, with simple tracking, in bold, dry wood fonts. The coherence and consistency of the visual identity is concluded, in the different digital platforms analyzed, with slight variations in the use of negatives and chromatography.